A Case of Traumatic Asphyxia due to Motorcycle Accident. (31st March 2013) - Kamali, Sedat; Kesici, Sevgi; Gunduz, Ihsan; Kesici, Ugur
Abstract : Background . Perthe's syndrome (traumatic asphyxia) is rare, which is caused by sudden compressive chest trauma and characterized by subconjunctival hemorrhage, facial edema, craniocervical cyanosis, and petechiae on the upper chest and face and should always be kept in mind as a possible complication of injuries of the chest and abdomen. Case Report . In this case report a 36-years-old male patient brought to the emergency room due to thorax trauma related to motorcycle accident was discussed. Distinct cyanotic, edematous, and multiple petechiae were present on the face, neck, and upper thorax regions of the patient. Bilateral subconjunctival hemorrhage was determined. Conclusion . Treatment for traumatic asphyxia is supportive and patient recovery is related to the generally associated injuries. Prognosis of the patients is quite good with effective and timely treatment.